Using Readability Tests to Improve the Accuracy of Evaluation Documents Intended for Low-Literate Participants - Kouamé, Julien B. (Journal of MultiDisciplinary Evaluation, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:1; mso-generic-font-family:roman; mso-font-format:other; mso-font-pitch:variable; mso-font-signature:0 0 0 0 0 0;} @font-face {font-family:Georgia; panose-1:2 4 5 2 5 4 5 2 3 3; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:647 0 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Arial","sans-serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page WordSection1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.WordSection1 {page:WordSection1;} --> <!--[if gte mso 10]> <![endif]--> Background: Readability tests are indicators that measure how easy a document can be read and understood. Simple, but very often ignored, readability statistics cannot only provide information about the level of difficulty of the readability of particular documents but also can increase an evaluator’s credibility. Purpose: The purpose of this article is two-fold: (1) to provide readers with logical reasons for using readability tests and (2) how to choose the right test for a project. Setting: United States. Research Design: A comparative framework is used to present the need for readability testing. Keywords: Readability tests, evaluation instruments, survey research, low-literacy survey